Isoliquiritigenin from licorice root: A multi-stage anti-malarial with synergistic impact on multidrug-resistant P. falciparum - Saurabh Kumar; Deepak Singh kapkoti; Pooja Rani Mina; Divya Bhatt; Parmanand Kumar; Manju Singh; Karuna Shanker; Dnyaneshwar Umrao Bawankule; Rajendra Singh Bhakuni; Anirban Pal; Mahendra P. Darokar (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Malaria control is hindered by drug-resistant parasites, leading to a shortage of effective drugs. There is a need to find new, better antimalarial drug. Traditional Chinese Medicine (TCM) are more accessible and cheaper alternative for combating resistance in the treatment of malaria, therefore the anti-malarial efficacy of root extracts and isolated phytomolecules from Glycyrrhiza glabra L was assessed. Methods: The anti-plasmodial potential of root extracts and isolated phytomolecules from Glycyrrhiza glabra L. was assessed using the Giemsa staining method. In- vivo, antimalarial efficacy was evaluated by conducting a four-day suppression test in a mouse model. The mechanistic studies of ISL were carried out using caspase-like activity, mitochondrial membrane potential, and reactive oxygen species (ROS) assay. Further, proteomics analysis was carried out by LC-MS/MS. The interaction of the combinations was evaluated using the fixed ratio method by calculating the fractional inhibitory concentration (FIC). Results: Extracts of G. glabra contain Phytomolecule(s) with moderate anti-plasmodial activity against multidrug-resistant strain (K1) of P. falciparum. Isoliquiritigenin (ISL) exhibited a significant reduction in parasitemia, resulting in an enhancement of the mean survival time in Plasmodium yoelii nigeriensis infected mice. ISL showed potent activity with no cytotoxic effect and increased caspase-3 activity, leading increasing reactive oxygen species (ROS) and loss of mitochondrial potential. ISL also displayed synergy with chloroquine, glabridin and liquiritigenin against multi-drug-resistant P. falciparum. Discussion: The present study found ISL to be a potential phytomolecule of G. glabra. The study explored the mechanism of action of ISL and suggested its suitability for further study in managing drug-resistant malaria.